2018
DOI: 10.1016/j.ibiod.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of Pinus radiata delays hydrolytic depolymerisation by the brown-rot fungus Rhondonia placenta

Abstract: Acetylation of wood can provide protection against wood deteriorating fungi, but the exact degradation mechanism remains unclear. The aim of this study was to determine the effect of acetylation of Pinus radiata wood (weight percent gain 13, 17 and 21%) on the expression of genes involved in decay by brown-rot fungus Rhodonia placenta. Gene expression analysis using qRT-PCR captured incipient to advanced decay stages. As expected the initiation of decay was delayed as a result the degree of acetylation. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 53 publications
4
41
0
Order By: Relevance
“…Hunt et al [26] reported a decreased diffusion of K + ions with an increasing level of acetylation, which supports the theory to be involved in their wood decaying system [64]. Oxaloacetate dehydrogenase (CyOx Ppl112832) is presumed to be involved in oxalic acid synthesis, which is important for sequestering and reducing Fe 3+ to Fe 2+ [13]. Glyoxylate dehydroxygenase (GlyD Ppl121561) is likely involved in oxalic acid synthesis, by catalyzing the production of oxalate through oxidation of glyoxalate [65].…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Hunt et al [26] reported a decreased diffusion of K + ions with an increasing level of acetylation, which supports the theory to be involved in their wood decaying system [64]. Oxaloacetate dehydrogenase (CyOx Ppl112832) is presumed to be involved in oxalic acid synthesis, which is important for sequestering and reducing Fe 3+ to Fe 2+ [13]. Glyoxylate dehydroxygenase (GlyD Ppl121561) is likely involved in oxalic acid synthesis, by catalyzing the production of oxalate through oxidation of glyoxalate [65].…”
Section: Introductionmentioning
confidence: 71%
“…Each sample was run with three technical replicates. β-tubulin was used as an endogenous control [13]. A list with all used primers including the number of the Joint Genome Institute (JGI) can be found in Table 2.…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
See 3 more Smart Citations